BIBLIOMETRIC ANALYSIS OF RESEARCH TRENDS IN ORGANIZATIONAL CHANGE MANAGEMENT - Nugraha, Evans Afriant; Dwianto, Agung Surya (PT. Jurnal Center Indonesia Publisher, 2025)
This study presents a systematic mapping of Change Management and Organizational Change research using bibliometric analysis. The specific objectives are to identify research development trends in this field and to visualize the keyword network for the period 2016–2025 using VOSviewer. Data were collected from Google Scholar via the Publish or Perish (PoP) software, with Mendeley utilized for reference management. The findings indicate that studies on organizational change management between 2016 and 2025 remain predominantly focused on internal organizational aspects, specifically structural transformation, leadership, intervention strategies, and employee resistance. The bibliometric visualization generated five main clusters centered on the core keyword